Strong Negative Interference by Calcium Dobesilate in Sarcosine Oxidase Assays for Serum Creatinine Involving the Trinder Reaction - Guo, Xiuzhi; Hou, Li’an; Cheng, Xinqi; Zhang, Tianjiao; Yu, Songlin; Fang, Huiling; Xia, Liangyu; Qi, Zhihong; Qin, Xuzhen; Zhang, Lin; Liu, Qian; Liu, Li; et al. (Medicine (Baltimore), 2015)
The vasoprotective drug calcium dobesilate is known to interfere with creatinine (Cr) quantifications in sarcosine oxidase enzymatic (SOE) assays. The aim of this study was to investigate this interference in 8 different commercially available assays and to determine its clinical significance. In in vitro experiments, interference was evaluated at 3 Cr levels. For this, Cr was quantified by SOE assays in pooled serum supplemented with calcium dobesilate at final concentrations of 0, 2, 4, 8, 16, 32, and 64 μg/mL. Percent bias was calculated relative to the drug-free specimen. For in vivo analyses, changes in serum concentrations of Cr, cystatin C (CysC; a renal function marker), and calcium dobesilate were monitored in healthy participants of group I before and after oral calcium dobesilate administration. In addition, variations in interference were also examined among different SOE assays using serum obtained from healthy participants of group II. Lastly, Cr levels from the 10 patients treated with calcium dobesilate were measured using 4 SOE assays and liquid chromatography-isotope dilution tandem mass spectrometry (LC-IDMS/MS) for comparison. Our in vitro analyses indicated that the presence of 8 μg/mL calcium dobesilate resulted in a -4.4% to -36.3% reduction in Cr serum concentration compared to drug-free serum for 8 SOE assays examined. In vivo, Cr values decreased relative to the baseline level with increasing drug concentration, with the lowest Cr levels obtained at 2 or 3 hours after drug administration in participants of group I. The observed Cr concentrations for participants in group II were reduced by -28.5% to -3.1% and -60.5% to -11.6% at 0 and 2 hours after administration related to baseline levels. The Cr values of 10 patients measured by Roche, Beckman, Maker, and Merit Choice SOE assays showed an average deviation of -20.0%, -22.4%, -14.2%, and -29.6%, respectively, compared to values obtained by LC-IDMS/MS. These results revealed a clinically significant negative interference with calcium dobesilate in all sarcosine oxidase-based Cr assays, but the degree of interference varied greatly among the assays examined. Thus, extra care should be taken in evaluating Cr quantification obtained by SOE assays in patients undergoing calcium dobesilate therapy.